Real-time A algorithm for optimal variable gain proportional-integral-derivative control systems - Cheok, K.C.; Huang, N.J. (Proceedings IEEE International Symposium on Intelligent Control 1988, 1988)
The application of heuristic search to optimal control systems is investigated. A modified algorithm known as real-time A* (RTA*) is proposed for online implementation of a heuristic optimal tracking control system. The heuristic forward search mechanism of the A* yields the same optimal path as the backward search of dynamic programming which is commonly used in the optimal control problem. A relationship between heuristic evaluation, f=g+h, and tracking performance measure, J, for the optimal tracking control systems is given. Experimental results are given to show the application of the heuristic search RTA* to an online optimal variable gain proportional-integral-derivative (OVGPID) control system.< >